Comprehensive proteomic analysis of sea cucumbers (Stichopus japonicus) in thermal processing by HPLC-MS/MS. (30th March 2022) - Gu, Pan; Qi, Shizhe; Zhai, Ziyang; Liu, Jing; Liu, Zheyi; Jin, Yan; Qi, Yanxia; Zhao, Qiancheng; Wang, Fangjun
Highlights: The total protein loss of sea cucumber in high pressure steaming was the lowest. Proteins undergoes unspecific hydrolysis during the thermal processing. The protein residues with the highest thermal-induced hydrolysis frequency were Phe, Leu, Asn, and Tyr. Abstract: Thermal processing is the most frequently adopted processing technology for sea cucumbers, which can significantly affect their protein composition. In this paper, three thermal processing methods high pressure steaming (HPS), atmospheric pressure boiling (APB), and atmospheric pressure steaming (APS) were adopted and protein compositions of both body walls and cooking liquors by thermal processing stichopus japonicus were systematically analysis by proteomic strategy. The total proteins loss rates of body walls were 11.6%, 13.0%, and 14.8% for HPS, APS, and APB methods, respectively. However, the main types of protein composition were retained. Similar mechanisms of protein loss may exist even if different thermal processing were applied. The most frequent hydrolysis sites in thermal processing were phenylalanine, leucine, asparagine, and tyrosine at both C and N terminals. This study provides theoretical guidance for optimizing the industry thermal processing of sea cucumbers.